Sosialisasi Penataan Pedagang Kaki Lima (PKL) Tangguh Pandemi di Pantai Losari Kota Makassar - Arifuddin Akil; Ananto Yudono; Shirly Wunas; Slamet Trisutomo; M. Yamin Jinca; Mukti Ali; Mimi Arifin; Abdul Rachman Rasyid; Ihsan Latief; Wiwik Wahidah Osman; Yashinta Kumala Dewi Sutopo; Sri Aliah Ekawati; M. Fathien Azmy; Marly Valenti Patandianan; Isfa Sastrawati; Gafar Lakatupa; Sri Wahyuni; Laode Muh. Asfan Mujahid; Jayanti A. Munawwara Abdu Mandasari; Suci Anugrah Yanti; Fitha Rachmah Sari; Andi Nur Jayadi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
Street vendors are one type of informal sector work that is very vulnerable to being affected by the Covid-19 pandemic. It also felt by street vendors in the Makassar Losari Beach Pavilion area. The condition of street vendors on the one hand is in contact with the lower middle class and has a relatively small business scale. Besides, organized and planned PKL activities will be able to adapt to pandemic conditions and have a positive impact on the city's local economy and support the government in providing employment. This service activity aims to present ideas for the concept of structuring street vendors that are resilient to pandemics and educating traders about the application of health protocols in the work environment of street vendors. Data collection techniques are observation, documentation, interviews, through a stakeholder approach. The data analysis technique is descriptive qualitative analysis. The data collected is used in arrange the concept of structuring street vendors that are resilient to pandemics, sharing, and transferring knowledge to street vendors in the form of Focus Group Discussions (FGD) accompanied by video playback of planning concept arrangements and education on the application of health protocols. The results of service activities in the form of the concept of structuring street vendors include the arrangement of stalls, tables and chairs, repair of clean water networks, provision of hand washing facilities, trash cans, garbage containers, and waste disposal schemes, as well as socializing the importance of implementing health protocols for traders and visitors.